Understanding Canadian Health Technology Assessment through a systems lens. Issue 9 (September 2020) - Lopes, Edilene; Street, Jackie; Carter, Drew; Merlin, Tracy; Stafinski, Tania
Highlights: Stakeholders emerge as the most influential aspect of the Canadian HTA system. Values and environment affect the entire system, especially stakeholder interactions. Stakeholders praise inclusive collaborations but criticise exclusive alliances. Industry-patient alliances may conflict with the interests of other stakeholders. Provincial governments need better patient and industry engagement. Abstract: Objective: Governments around the world face challenges in maintaining sustainable, high-quality healthcare systems. Health Technology Assessment (HTA) is widely used as a method to assist in funding decisions. However, the scope and influence of HTA is still limited. We examined how policymakers can improve the usefulness of HTA. Methods: We used Systems Thinking as a theoretical framework to examine HTA as a system. We purposely sampled stakeholders involved in Canadian HTA at a national or provincial level. We conducted 22 semi-structured interviews in September-December 2016. Data were analysed using NVivo10 and findings are presented as a concept map with explanatory text. Findings: The HTA system is influenced by stakeholder interactions. Such interactions are, in turn, affected by stakeholders' worldviews and environmental factors. Stakeholders' worldviews includes individual's or groups' values and affect the exchange of information, and interpretation of events. External factors, such as changes to government structures, also affect the system. Conclusion: Most stakeholder groups are supportive of the system. However, participants identified a need for change, though the exact changes being recommended differed. Some interactions were praised (formal, inclusive collaborations to provide government with policy guidance on both broad and technology-specific matters), while other interactions were criticised (two-party alliances formed around purposes other than the common good, and lacklustre patient and industry engagement on the part of provincial government).